Relational Trust: The Glue that Binds a Professional Learning Community - Cranston, Jerome (Alberta Journal of Educational Research, 2011)
This article examines how principals describe the nature of relationships and presence (or absence) of relational trust among teachers, and between the teachers and the principal in the discourse of professional learning communities. Participants were 12 school principals from urban, suburban, and rural communities in Manitoba. In the discourse of learning communities, the notion of trust is articulated as being relational in its orientation and developed around group norms of safety, risk-taking, and change orientation. The existence of relational trust appears to have the effect of fostering collaboration and promoting willingness among staff to grow professionally. The study also suggests the important role that principals play in establishing relational trust as a precondition for the growth of a professional learning community. Because relational trust appears to be critical to the functioning of a professional learning community, it may be unlikely that substantive school improvement can be achieved without close attention to it. Cet article porte sur la description que font les directeurs d'école de la nature des rapports des enseignants entre eux, des rapports entre les enseignants et le directeur, et de la présence ou l'absence de confiance relationnelle dans le contexte de communautés professionnelles d'apprentissage. Douze directeurs d'école de communautés urbaines, rurales et de banlieue du Manitoba ont participé à l’étude. Dans le discours des communautés d'apprentissage, on décrit la notion de confiance comme ayant une orientation relationnelle et en termes de développement des normes collectives touchant la sécurité, la prise de risque et l’orientation vers le changement. L'existence de la confiance relationnelle semble favoriser la collaboration et promouvoir la volonté chez le personnel de s'épanouir sur le plan professionnel. L'étude évoque également le rôle important que jouent les directeurs d'école dans l'établissement de la confiance relationnelle comme condition préalable pour l'épanouissement d'une communauté professionnelle d'apprentissage. La confiance relationnelle semblant être critique au fonctionnement d'une communauté professionnelle d'apprentissage, il est peu probable qu'une amélioration significative puisse avoir lieu dans une école si on n’y prête pas attention.